2018
DOI: 10.3390/e20080595
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Irreversible Desiccant Systems

Abstract: A new general thermodynamic mapping of desiccant systems' performance is conducted to estimate the potentiality and determine the proper application field of the technology. This targets certain room conditions and given outdoor temperature and humidity prior to the selection of the specific desiccant material and technical details of the system configuration. This allows the choice of the operative state of the system to be independent from the limitations of the specific design and working fluid. An expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Kanakubo et al suggested that the dehumidification capability of the ILs was dependent on not the cationic part but the anionic part of the IL [ 36 ]. Since many types of ILs have a moisture absorbent property, ILs are proposed as a desiccant source for the liquid desiccant type air-conditioning system [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. Luo et al attempted to use of several ILs as desiccants for an air conditioner [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanakubo et al suggested that the dehumidification capability of the ILs was dependent on not the cationic part but the anionic part of the IL [ 36 ]. Since many types of ILs have a moisture absorbent property, ILs are proposed as a desiccant source for the liquid desiccant type air-conditioning system [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. Luo et al attempted to use of several ILs as desiccants for an air conditioner [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al attempted to use of several ILs as desiccants for an air conditioner [ 37 , 38 ]. Zegenhagen [ 41 ], Verela [ 42 ], and Giannetti [ 43 , 44 ] also demonstrated the use of ILs as desiccant materials for an air-conditioning system. We recently reported that tributyl(methyl)phosphonium dimethylphosphate ([P 4441 ][DMPO 4 ]) displayed an excellent dehumidification capability; the [P 4441 ][DMPO 4 ] aqueous solution (77%(w/w)) could be used as a desiccant for a liquid desiccant air conditioner [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mu and co-workers proposed that water molecules in the air are captured by [C 2mim ]­[OAc] through the formation of four hydrogen bonds with an ion pairtwo hydrogen bonds with two oxygen atoms of the acetate anion and two more bonds with hydrogen atoms at the 4- and 5-positions of the [C 2mim ] cation . Due to the hygroscopic nature of ILs, their feasibility as desiccants for air conditioners has been studied by many groups, including us. Luo et al identified several imidazolium-based ILs as potential desiccants for air conditioners, , while Feycon reported that choline carboxylate ILs, cholin (2-hydroxy- N , N , N -trimethylethan-1-aminium) alkylcarboxylates ([Ch]­[RCO 2 ]), acted as an efficient desiccant . Aparicio et al proposed a water capture mechanism of [Ch]­[Lac] based on their DFT simulation study .…”
Section: Introductionmentioning
confidence: 99%
“…Another matter is related to the refrigeration industry, regarding the use of cooling fluids [ 5 ]. A liquid desiccant absorption system is one option for a vapor compression cooling system [ 6 , 7 , 8 ]. A Previous investigation [ 9 ] has shown that it is possible to achieve a reduction in overall energy consumption, although it has high initial system costs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%